2017
DOI: 10.19184/bisma.v11i2.6308
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Partisipasi Anggaran Terhadap Kinerja Manajerial Melalui Komitmen Organisasi Dan Motivasi

Abstract: This study aimed to analyze the effect of budget participation on managerial performance with organizational commitment and motivation as the intervening variables. Data were collected by distributing questionnaires to structural officials of the Government of Bondowoso Regency. The collected data were then analyzed using Structural Equation Modeling (SEM). Results showed that budget participation has significant and positive effect on managerial performance. Budget participation also has a positive and signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
1
3
0
4
Order By: Relevance
“…Therefore, it can be concluded that the variable budget participation has a positive effect on managerial performance. The results of this study are in line with the results of research conducted by Murwaningsari (2008), Noor and Othman (2012), Saraswati and Aisyah (2015), Savitri et al (2015), Gunawan and Santioso, (2015), Hariyanti et al (2015), and Ernis et al (2017) which show the positive influence of budget participation on managerial performance directly. Budget participation can increase understanding, effort, and motivation of managers in achieving budget targets and can improve the quality of the budget which will lead to enhance managerial performance of managers.…”
Section: Hypothesis Test Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Therefore, it can be concluded that the variable budget participation has a positive effect on managerial performance. The results of this study are in line with the results of research conducted by Murwaningsari (2008), Noor and Othman (2012), Saraswati and Aisyah (2015), Savitri et al (2015), Gunawan and Santioso, (2015), Hariyanti et al (2015), and Ernis et al (2017) which show the positive influence of budget participation on managerial performance directly. Budget participation can increase understanding, effort, and motivation of managers in achieving budget targets and can improve the quality of the budget which will lead to enhance managerial performance of managers.…”
Section: Hypothesis Test Resultssupporting
confidence: 91%
“…The relationship between the success of the budget compiled in a participative way with the achievement of budgetary goals and managerial performance has been found in many previous studies. Murwaningsari (2008), Noor and Othman (2012), Saraswati and Aisyah (2015), Gunawan and Santioso (2015), Hariyanti et al (2015), Boujelbene and Affes (2015), Ernis et al (2017), and Oyewo and Adyeye (2018) have proved that budget participation can enhance managerial performance. Further studies by Lameira Silva et al (2020) show budgetary participation directly and positively influences managerial attitudes toward budgeting, job satisfaction, and controllers' performance in budget activities.…”
Section: The Effect Of Budget Participation On Managerial Performancementioning
confidence: 98%
See 2 more Smart Citations
“…Komitmen organisasi yang massif menstimulus para eksekutif bawah menggapai dan menambah kinerja organisasi [3]. Melalui komitmen yang tinggi, pada saat mereka terlibat dalam penyusunan anggaran, mereka akan berbuat sesuatu yang lebih baik untuk menunjang keberhasilan organisasi dibandingkan untuk kepentingan sendiri [5].…”
Section: Pendahuluanunclassified